FINANCIAL OVERVIEW OF RIO DE JANEIRO CLUBS BETWEEN 2006 AND 2011 (Fiep Bulletin - online, 2013)
The four major football clubs in Rio de Janeiro experienced a period without victories in the early 2000s. However, from 2006 onwards, the scenario has changed. With three titles in the Brazil Cup and two in the Brazilian Championship, Botafogo, Flamengo, Fluminense and Vasco returned to the best places in national tournaments. Through descriptive analysis with empirical-analytic, the present study aimed to justify the recent success of teams from Rio de Janeiro using economic variables for the research. The results demonstrate that the clubs have poor financial situation, but suggest that the increase occurred in revenues and investments provided better sports performance in recent seasons.
Keywords: Football; Sports Performance; Economic Performance.